Diastolic Dysfunction in Hypertension - Nazário Leão, R (2017)
Hypertension and coronary heart disease, often coexisting, are the most common risk factors for heart failure. The progression of hypertensive heart disease involves myocardial fibrosis and alterations in the left ventricular geometry that precede the functional change, initially asymptomatic. The left ventricular diastolic dysfunction is part of this continuum being defined by the presence of left ventricular diastolic dysfunction without signs or symptoms of heart failure or poor left ventricular systolic function. It is highly prevalent in hypertensive patients and is associated with increased cardiovascular morbidity and mortality. Despite its growing importance in clinical practice it remains poorly understood. This review aims to present the epidemiological fundamentals and the latest developments in the pathophysiology, diagnosis and treatment of left ventricular diastolic dysfunction.